The E3 ligase CUL3/RDX controls centromere maintenance by ubiquitylating and stabilizing CENP-A in a CAL1-dependent manner - Bade, Debora; Pauleau, Anne-Laure; Wendler, Astrid; Erhardt, Sylvia (Developmental cell, 2014)
Centromeres are defined by the presence of the histone H3 variant CENP-A in a subset of centromeric nucleosomes. CENP-A deposition to centromeres depends on a specialized loading factor from yeast to humans that is called CAL1 in Drosophila. Here, we show that CAL1 directly interacts with RDX, an adaptor for CUL3-mediated ubiquitylation. However, CAL1 is not a substrate of the CUL3/RDX ligase but functions as an additional substrate-specifying factor for the CUL3/RDX-mediated ubiquitylation of CENP-A. Remarkably, ubiquitylation of CENP-A by CUL3/RDX does not trigger its degradation but stabilizes CENP-A and CAL1. Loss of RDX leads to a rapid degradation of CAL1 and CENP-A and to massive chromosome segregation defects during development. Essentially, we identified a proteolysis-independent role of ubiquitin conjugation in centromere regulation that is essential for the maintenance of the centromere-defining protein CENP-A and its loading factor CAL1.